The Effect of Land Cover Change on Soil Properties around Kibale National Park in South Western Uganda - J. G. M. Majaliwa; R. Twongyirwe; R. Nyenje; M. Oluka; B. Ongom; J. Sirike; D. Mfitumukiza; E. Azanga; R. Natumanya; R. Mwerera; B. Barasa (Applied and Environmental Soil Science)
The change from natural forest cover to tea and Eucalyptus is rampant in protected areas of western Uganda. The objectives were; to examine the trend in land-use /cover change and determine the effect of these changes on the physico-chemical properties of soils around Kibale National Park. The trend in land use/cover change was assessed by analyzing a series of landsat images. Focused group discussions and key informant interviews were used for land-use/cover reconstruction. Three major land uses were included; woodlot (Eucalyptus grandis; 5 years old) ), tea (57 years old) and natural forest used as a control. Each of these land-uses were selected at two different North facing landscape positions and were replicated three times. A total of 36 composite soil samples were taken at 0–15 and 15–30 cm depth from natural forest, Tea plantation and eucalyptus on three ridges. Results showed that small scale farming, tea and eucalyptus plantation and built up area have increased over time, to the expense of woodlot and forest cover. Tea and Eucalyptus have induced changes in: exchangeable Mg and Ca, available P, SOM, pH, and bulk density of sub soil (P<.05). Landscape positions within land use also significantly influenced most soil properties (P<.05). Similar findings were observed by Wang et al. (2006) in commercial tea plantations in China that received nitrogen fertilizers.